Position transducers for numerically controlled machine tools - Charnley, C. J. (College of Aeronautics, 1964)
The paper covers the basic text book theory of all forms of position transducer used on commercial numerically controlled machine tools. Some attempt is made to categorise and indicate the scope and usage of these devices. The descriptions deliberately set out to explain this essentially electrical topic in a manner not requiring expert electrical knowledge.